Continuing teacher training in environmental education: an analysis of the organizations involved in its development (Praxis Educativa, 2026)
This article examines Continuous Teacher Education (CTE) initiatives in Environmental Education (EE) in Argentina between 2021 and 2025, that is, since the enactment of the Comprehensive Environmental Education Law (Law 27,621). The analysis focuses on initiatives with national or inter-provincial scope (covering two or more provinces) and on the organizations responsible for their design and implementation, with illustrative cases from the provinces of Santa Fe and Mendoza included. Key findings reveal that CTE in EE is promoted and delivered by a diverse and heterogeneous range of institutions, many of which operate outside the formal education sector, thereby evidencing the emergence of public–private partnerships and the growing marketisation of CTE in the country.
Keywords: environmental education; continuous teacher education; organization; educational policies; Argentina